2009
DOI: 10.17221/261-pse
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of variation in lipophilic and hydrophilic constituents in flower developmental stages of Echinacea purpurea (L.) Moench cultivated in Slovakia

Abstract: The objective of this study was to examine and demonstrate how harvesting age (flower age) contribute to the variations in the quality of Echinacea purpurea (L.) Moench. The effects of different flower developmental stages on caffeic acid derivatives and isobutylamide content are described. These phytochemicals were extracted from fresh plants with 60% ethanol and quantified by the HPLC analysis. The results revealed that the quality of Echinacea is strongly influenced by the flower developmental stages. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…However, they exhibited higher bioactive properties with the late harvest in 2010. Complying with the present findings, Mistríková and Vaverková (2009) reported that the amount of hydrophilic and lipophilic compounds of Echinacea's flower was higher during the third (ripening) developmental stage compared to the earlier stages, thus the third developmental stage was the best time for harvest. Chen et al (2008) determined that the total phenolic contents in E. purpurea harvested in the spring were lower than that of the plants harvested in the autumn.…”
Section: Resultssupporting
confidence: 89%
“…However, they exhibited higher bioactive properties with the late harvest in 2010. Complying with the present findings, Mistríková and Vaverková (2009) reported that the amount of hydrophilic and lipophilic compounds of Echinacea's flower was higher during the third (ripening) developmental stage compared to the earlier stages, thus the third developmental stage was the best time for harvest. Chen et al (2008) determined that the total phenolic contents in E. purpurea harvested in the spring were lower than that of the plants harvested in the autumn.…”
Section: Resultssupporting
confidence: 89%
“…For example, the abundance of caffeic acid derivatives and isobutylamides in the flower heads of Echinacea purpurea (L.) Moench was found to be closely correlated with their developmental stage [62,63] (Fig. 1).…”
Section: Adulteration and Substitutionmentioning
confidence: 99%
“…The research we have conducted is aimed at systematical studies of the composition of essential oils in various medicinal plants (Farkas et al 2003, Mistrikova andVaverkova 2009) with a special focus on the influence of pesticides on the composition of these essential oils (Vaverkova et al 1997). Essential oils from Mentha × piperita exhibit a high level of antifungal activity and they are comparable to synthetic fungicides (Farkas et al 2003, Hadian et al 2008).…”
mentioning
confidence: 99%